Evaluasi Sistem Informasi Pelayanan Rekam Medis di RSJ Prof. Dr. V.L. Ratumbuysang Provinsi Sulawesi Utara dengan Pendekatan Hot Fit Model - Donny Makalalag; Farid Agushybana; Atik Mawarni (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2017)
Medical Record Information System Service at Prof. Dr. V.L. Ratumbuysang Mental Hospital North Sulawesi Province had not run as expected. Indicated by the differences in patient data in the recording and the medical records. Factors that allegedly affect are human, organization and technology. This study aims to evaluate medical record service information system with the HOT FIT Model approach and its benefits. This was a qualitative study. Data collected through in depth interviews and analyzed by content analysis method. Research subjects were 1 admin officer and 3 archival officers as main informants and the chief of medical record service, the head medical services division and an assistant director of medical services and nursing as the triangulation informants. The results showed that the medical record service information system had facilitated the work but the knowledge and skills of the officers were still lacking. Organizational factors were supported but the budget was still lacking in system development. Technological factors had not run optimally because the LAN network did not work. The quality of the information had not been met because the data of the visits should be checked again before used for decision making. Quality of service was not maximal yet, because the connectivity between medical record and polyclinic was impaired, then the officer used manual form. It can be concluded that the hospital need to increase the staff knowledge and allocate funds for improvement and development of information systems or cooperate with other parties in system maintenance.